2005
DOI: 10.2320/matertrans.46.872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Film Thickness on Structural and Electrical Properties of Sputter-Deposited Nickel Oxide Films

Abstract: This work studies dependences of resistivity, carrier concentration, mobility and structural properties on the thickness of nickel oxide (NiO) films deposited onto glass substrates by RF magnetron sputtering in a pure oxygen atmosphere at an RF power 200 W. The electrical properties were measured by Hall Effect measurements. The X-ray diffraction (XRD) and transmission electron microscope (TEM) analyses of nickel oxide films indicates that these films are polycrystalline when the samples are prepared with an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…In Fig, 1, first absorption band that is visible at 403 cm¯ related to the stretching vibrations of Ni-O bond of nickel oxide [15]. The peak at 505 cm -1 is due to ZnO [16] .The band which is recorded at 1110 cm¯ corresponds to the stretching vibrations of C-O-C [17]. The absorption bands located at 1401 cm -1 and 1642 cm −1 is due to the stretching vibration of C-O and C=O groups respectively 1 [17].…”
Section: Resultsmentioning
confidence: 98%
“…In Fig, 1, first absorption band that is visible at 403 cm¯ related to the stretching vibrations of Ni-O bond of nickel oxide [15]. The peak at 505 cm -1 is due to ZnO [16] .The band which is recorded at 1110 cm¯ corresponds to the stretching vibrations of C-O-C [17]. The absorption bands located at 1401 cm -1 and 1642 cm −1 is due to the stretching vibration of C-O and C=O groups respectively 1 [17].…”
Section: Resultsmentioning
confidence: 98%
“…Then, the 100 nm thickness of nickel oxide was deposited as a sensitive layer by reactive RF sputter at room temperature and then it was patterned by lift-off method (6). For the forming self-supporting structure of the micro-bridge, Si 3 N 4 and PI was removed by RIE and oxygen plasma asher, respectively (7,8). The fabricated micro-bolometer structure was inspected by using field emission scanning electron microscopy (FE-SEM).…”
Section: Resultsmentioning
confidence: 99%
“…The conductivities NiO Films Formed at Room Temperature for Microbolometer in nickel oxides are strongly dependent on microstructure defects of nickel oxides crystallites such as nickel vacancies and interstitial oxygen atoms. Furthermore, deposition conditions and environments generating microstructure distortion and non-stoichiometry are the main factors affecting the electrical conductivities in nickel oxides [8].…”
Section: Resultsmentioning
confidence: 99%
“…Lalitha et al [23] and El-kadry et al [24] reported that a decrease in internal micro-strain in materials causes an increase in the crystallite size. Additionally, Chen et al elaborated that decrease in micro-strain leads to a reduction in inter-planar spacing and this minimizes the stacking fault probability in the materials [25]. Hence, it is assumed here that biofield energy treatment might cause a decrease in internal microstrain and this lead to a decrease in the inter-planar spacing and resultant increase in the crystallite size.…”
Section: Fig 1 Xrd Diffractograms Of Control and Treated 26-dichlomentioning
confidence: 98%